CHARACTER EDUCATION IN AHMAD FUADI’S NEGERI 5 MENARA - Muhammad Tahir (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Character Education is indeed a high priority,   the process of facilitating learning, or the acquisition of knowledge, skills, values, beliefs, and habits. Character education is not a process of transfering knowledge and memorizing the materials to have an exam. Character education requires habituation. It refers to real action of becoming caring, perseverance, and team work, being ashamed to cheat and also being ashamed to be lazy. Character Education is indeed a high priority, one of the important factors in determining a country’s development. It can bring a country in advance or even in decline. Education has important role to create and develop young generations’ potential to have the the spiritual strength of religious, include caring, confidence, caurage, curiosity, flexibility, friendship, goal setting, humility, humor, initiative, integrity, patience, perseverance, positive attitude, problem solving, self discipline, teamwork, and the skills needed for themselves and society. The points of discussion in this study are Caring, Perseverance and Teamwork with a purpose to find out and describe the traits of characters education found in the novel. The research is conducted by means of descriptive qualitative research proposed by Creswell (2009) and Ary (2002) The results show that the three traits Caring, Perseverance and Teamwork are found in the novel.